The transformation of the student career : university study in Germany, the Netherlands, and Sweden - Nugent, Michael A. (RoutledgeFalmer studies in higher education (Unnumbered), 2004)
This study examines the transformation of the structural characteristics and ideological assumptions of university study in these three countries between the mid-1950s and the early 1990s.